Comparative Study of Performance between International Roughness Index (IRI), Pavement Condition Index (PCI), and Bina Marga Method on Roadways - St Maryam H; Bulgis Bulgis; Rustam Madami (Faculty of Engineering, Andi Djemma University, 2023)
In this research, a comparative study is conducted between the International Roughness Index (IRI), Pavement Condition Index (PCI), and Bina Marga method on roadways with a flexible pavement structure. The objective is to compare the results of road damage evaluation using these three methods and formulate appropriate treatment programs. The research findings indicate that overall, the IRI method provides an overview of the road surface roughness level. The majority of the analyzed data falls under the